High‐resolution diffusion‐weighted imaging of the breast with multiband 2D radiofrequency pulses and a generalized parallel imaging reconstruction. Issue 1 (17th January 2016) - Taviani, Valentina; Alley, Marcus T.; Banerjee, Suchandrima; Nishimura, Dwight G.; Daniel, Bruce L.; Vasanawala, Shreyas S.; Hargreaves, Brian A.
Abstract : Purpose: To develop a technique for high‐resolution diffusion‐weighted imaging (DWI) and to compare it with standard DWI methods. Methods: Multiple in‐plane bands of magnetization were simultaneously excited by identically phase modulating each subpulse of a two‐dimensional (2D) RF pulse. Several excitations with the same multiband pattern progressively shifted in the phase‐encode direction were used to cover the prescribed field of view (FOV). The phase‐encoded FOV was limited to the width of a single band to reduce off‐resonance‐induced distortion and blurring. Parallel imaging (PI) techniques were used to resolve aliasing from the other bands and to combine the different excitations. Following validation in phantoms and healthy volunteers, a preliminary study in breast cancer patients (N=14) was performed to compare the proposed method to conventional DWI with PI and to reduced‐FOV DWI. Results: The proposed method gave high‐resolution diffusion‐weighted images with minimal artifacts at the band intersections. Compared to PI alone, higher phase‐encoded FOV‐reduction factors and reduced noise amplification were obtained, which translated to higher resolution images than conventional (non‐multiband) DWI. The same resolution and image quality achievable over targeted regions using existing reduced‐FOV methods was obtained, but the proposed method also enables complete bilateral coverage. Conclusion: We developed an in‐plane multiband technique for high‐resolution DWI and compared its performance with other standard DWI methods. Magn Reson Med 77:209–220, 2017. © 2016 Wiley Periodicals, Inc.